FORMATION OF METAL AND SILICATE GLOBULES IN GUJBA: A NEW BENCUBBIN-LIKE METEORITE FALL - Rubin A.E.; Kallemeyn G.W.; Wasson J.T.; Clayton R.N.; Mayeda T.K.; Grady M.; Verchovsky A.B.; Eugster O.; Lorenzetti S. (My University, 2003)
Gujba is a coarse-grained meteorite fall composed of 41 vol% large kamacite globules, 20 vol% large light-colored silicate globules with cryptocrystalline, barred pyroxene and barred olivine textures, 39 vol% dark-colored, silicate-rich matrix, and rare refractory inclusions. Gujba resembles Bencubbin and Weatherford in texture, oxygen-isotopic composition and in having high bulk δ15N values (~+685%%). The 3He cosmic-ray exposure age of Gujba (26 +/- 7 Ma) is essentially identical to that of Bencubbin, suggesting that they were both reduced to meter-size fragments in the same parent-body collision. The Gujba metal globules exhibit metal-troilite quench textures and vary in their abundances of troilite and volatile siderophile elements. We suggest that the metal globules formed as liquid droplets either via condensation in an impact-generated vapor plume or by evaporation of preexisting metal particles in a plume. The lower the abundance of volatile elements in the metal globules, the higher the globule quench temperature. We infer that the large silicate globules also formed from completely molten droplets; their low volatile-element abundances indicate that they also formed at high temperatures, probably by processes analogous to those that formed the metal globules. The coarse-grained Bencubbin-Weatherford-Gujba meteorites may represent a depositional component from the vapor cloud enriched in coarse and dense particles. A second class of Bencubbin-like meteorites (represented by Hammadah al Hamra 237 and QUE 94411) may be a finer fraction derived from the same vapor cloud.